2020
DOI: 10.20944/preprints202010.0641.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aging-induced Changes in Sperm DNA Methylation are Modified by Low Dose of Perinatal Flame retardants

Abstract: Advanced paternal age at fertilization has been suggested to be a risk factor for neurodevelopmental, psychiatric and other disorders in offspring. One emerging hypothesis suggests that altered offspring phenotype is linked with age-related accumulation of epigenetic changes in the sperm of fathers. Given that paternal age is increasing in the developed world, understanding aging-related epigenetic changes in sperm is needed as well as environmental factors that modify such changes. In this study, we character… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Interestingly, another study from our group, using the same rat model, reported similar effects of BDE-47 exposure on age-dependent changes in sperm DNA methylation [ 35 ]. In this study, exposure had minor effects on DNA methylation when exposed and control animals of the same age were compared.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Interestingly, another study from our group, using the same rat model, reported similar effects of BDE-47 exposure on age-dependent changes in sperm DNA methylation [ 35 ]. In this study, exposure had minor effects on DNA methylation when exposed and control animals of the same age were compared.…”
Section: Discussionmentioning
confidence: 79%
“…Protein-coding genes—targets of piRNA and miRNA (11)—were enriched with categories related to embryonic development (12). Numbers shown in red stars indicate findings concordant with the analysis of DNA methylation in the same rat model [ 35 ]: 3—exposure to BDE-47 had a minor effect on DNA methylation if exposed and control animals of the same age were compared; 4—age-dependent differences in DNA methylation were significant in control animals; 5—these differences were attenuated by BDE-47 exposure due to the “convergence” effect, 11—gene targets of age-dependent sncRNA and genes associate with age-dependent differentially methylated regions of DNA overlapped significantly; 12—these genes were highly enriched for embryonic development.…”
Section: Figurementioning
confidence: 89%
See 1 more Smart Citation
“…Epigenetic programming is essential for post-fertilization success and offspring healthy development in the mammal's gametes. 105,106 Abnormal spermatozoa quality is associated with alternative DNA methylation in imprinted regions of the genes that play a vital role in reproduction. In mammals, it has been shown that spermatozoa concentration, motility and morphology are associated with DNA methylation levels.…”
Section: Imprintingmentioning
confidence: 99%
“…168 The age-related differentially methylated regions (DMRs) in rat spermatozoa were shown to be enriched for embryonic development. 106 The multiple age-associated DMRs in human spermatozoa were used to speculate chronological age with high accuracy. 169 Recently, spermatozoa ageing has been an important topic in aquaculture management, particularly as short-term storage sperm are used for artificial reproduction.…”
Section: Spermatozoa Ageingmentioning
confidence: 99%